2005
DOI: 10.1007/s11746-005-1147-5
|View full text |Cite
|
Sign up to set email alerts
|

Deacidification of soybean oil using supercritical fluid and membrane technology

Abstract: Membrane processing has been used for oil purification, but low flux and membrane instability are major impediments. A technique that combines membrane processing and supercritical CO 2 was investigated. A specialized, high-pressure, dead-end membrane cell was designed, fabricated, and connected to two ISCO (Lincoln, NE) supercritical fluid extraction (SFE) systems. The cell has a base with a grooved bottom for permeate removal, plus a porous metal disc for membrane support; a cell body with threaded connectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
(18 reference statements)
2
19
0
1
Order By: Relevance
“…1. The system has been described in detail previously [4,5] and the same equipment set-up was used with slight modifications, e.g., a co-solvent pump was not used in this experiment. A supercritical extractor SFX-210 and a 100DX syringe pump with 100 mL capacity (ISCO Inc., Lincoln, NE) and with temperature control and monitoring systems were used for the solubility and membrane studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The system has been described in detail previously [4,5] and the same equipment set-up was used with slight modifications, e.g., a co-solvent pump was not used in this experiment. A supercritical extractor SFX-210 and a 100DX syringe pump with 100 mL capacity (ISCO Inc., Lincoln, NE) and with temperature control and monitoring systems were used for the solubility and membrane studies.…”
Section: Methodsmentioning
confidence: 99%
“…Fats and oils could be selectively extracted using pressurized fluids, but the capital costs are very high, which makes this process unattractive economically. Research done by Artz et al [4,5] on the use of supercritical carbon dioxide in combination with membrane technology indicated that the technology shows promise for the deacidification of crude vegetable oil. However, the processing conditions required for supercritical fluids greatly exceed those normally used for membrane processing, which presents some difficult technical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of recompression of CO 2 to liquid or supercritical state is high. In this sense, coupling SFE to membrane separation allows keeping CO 2 in the process conditions, resulting in a significant energetic economy in terms of recompression costs [118,122,123]. Another advantage is the possibility to operate with high permeate flux, due to the low viscosity of supercritical CO 2 (ten times lower than water, with diffusivity 10 to 100 times higher [116,118].…”
Section: Membrane Separation Technologymentioning
confidence: 99%
“…Both alternatives lead to additional costs, directly related to the need of security equipment, more energy expenses, and other separation procedures needed for environmentally reasons, and also to degradation of the product. In this sense, a new crossflow filtration process was proposed, taking advantage of the low viscosity and superficial tension of supercritical CO 2 [123,126,127]. Indeed, this process increases the quality of the product and is environment friendly.…”
Section: Membrane Separation Technologymentioning
confidence: 99%
“…Another potential solution is the use of hybrid processes, i.e. the supercritical CO 2 process combined with membrane technology (Koseoglu 1991;Artz et al 2005;Lai et al 2008).…”
Section: Introductionmentioning
confidence: 99%